Recent advances in immunopathogenesis and clinical practice: mastering the challenge-managing of non-tuberculous mycobacteria - Chancharoenthana, Wiwat; Kamolratanakul, Supitcha; Rotcheewaphan, Suwatchareeporn; Leelahavanichkul, Asada; Schultz, Marcus J. (Frontiers in Immunology, 2025)
Non-tuberculous mycobacteria (NTM) are widespread environmental pathogens that can lead to significant disease burden, particularly in immunocompromised individuals, but also in those with a normal immune system. The global incidence of NTM is increasing rapidly, with Mycobacterium avium complex (MAC) being one of the most common types. The immunopathogenesis of the MAC involves a complex interaction between the bacteria and the host immune system. MAC survives and replicates within macrophages by preventing the fusion of phagosomes and lysosomes. The mycobacteria can neutralize reactive oxygen and nitrogen species produced by the macrophages through their own enzymes. Additionally, MAC modulates cytokine production, allowing it to suppress or regulate the immune response. Diagnosing MAC infections can be challenging, and the effectiveness of available treatments may be limited due to MAC’s unpredictable resistance to various antimycobacterial drugs in different regions. Treating MAC infection requires a collaborative approach involving different healthcare professionals and ensuring patient compliance. This review aims to shed light on the complexities of MAC infection treatment, discussing the challenges of MAC infection diagnosis, pharmacological considerations, such as drug regimens, drug monitoring, drug interactions, and the crucial role of a multidisciplinary healthcare team in achieving the best possible treatment outcomes for patients.